Distribution and Characteristics of Javan Hawk Eagle Nesting Trees in Gunung Halimun Salak National Park, Indonesia - Wardi Septiana; Ahmad Munawir; Pairah Pairah; Moch. Erlan Sodahlan; Yosi Irawan; Yanto Santosa; Lilik Budi Prasetyo (Jurnal Biodjati, 2020)
Javan Hawk Eagle is one of the three keys species of the Gunung Halimun Salak National Park and endemic to the island of Java. Protecting the active Javan Hawk Eagle nesting tree is one of the efforts to increase the success rate of Java Hawk Eagle breeding so that information on the distribution and characteris-tics of Javan Hawk Eagle nesting tree is needed. Field exploration was carried out to determine the existence of the Javan Hawk Eagle nest. There were 10 individuals of Javan Hawk Eagle nesting trees which consisted of 5 species namely Rasamala, Huru, Damar, Leng-sar and Manggong with tree architecture models of rauh, massart, scarrone and aubreville, tree height between 26-55 m and height of nests between 18-41m. The Javan Hawk Eagle nesting trees grow in primary, secondary, and plantation forests in a height between 670- 1295 masl, with a steep and very steep slope, the majority of the dis-tance from the river is less than 100 m and the majority of the dis-tance with ecotone is less than 600 m. Javan Hawk Eagle nest on Damar is the first finding at Gunung Halimun Salak National Park.